Sources Of Education Funds In School Review From The Perspective Of The Indonesian Education Financial System - Gunawan, Gunawan; Siahaan, Amiruddin (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2021)
Basically the 1945 Constitution has mandated that the fulfillment of the right to education is the responsibility of the state. That is, normatively the state should be the party most responsible for the fulfillment of the right to education. In any case, the state should not waive its responsibility for the financing of education. On the other hand, the state through the government must continue to disseminate education financing by referring to standard standards, especially regarding education components, curriculum, teaching and learning processes, and graduation competency targets. The use of education funding must be regulated because apart from APBN/APBD funds, education funds can also be collected from the community through educational institutions. There are 7 (seven) sources of education financing, namely: Sources of funds from the central government, regional governments, parents, foster parents, community groups, students themselves and sourced from foundations. In this research, the method used is library research by collecting information and data with the help of various materials in the library such as reference books, similar previous research results, articles, notes, and various journals related to the problem to be solved. Activities are carried out systematically to collect, process, and conclude data using certain methods/techniques in order to find answers to problems faced by activities in research. In this research, the method used is library research by collecting information and data with the help of various materials in the library such as reference books, similar previous research results, articles, notes, and various journals related to the problem to be solved. Activities are carried out systematically to collect, process, and conclude data using certain methods/techniques in order to find answers to problems faced by activities in research. In this research, the method used is library research by collecting information and data with the help of various materials in the library such as reference books, similar previous research results, articles, notes, and various journals related to the problem to be solved. Activities are carried out systematically to collect, process, and conclude data using certain methods/techniques in order to find answers to problems faced by activities in research.